Acid proteinase, phospholipase and adherence properties of Candida parapsilosis strains isolated from clinical specimens of hospitalised patients - KARAVUŞ, MELDA; ÇERİKÇİOĞLU, NİLGÜN (WILEY, 2005)
In this study, we investigated the presence of virulence factors in a total of 33 Candida parapsilosis strains, including adherence, acid proteinase and phospholipase production capabilities. Of the 33 strains, 19 were isolated from blood cultures of hospitalised fungaemic patients (study group 2). We also investigated the importance of other factors present in the development of fungaemia. The mean adherence values of 19 blood isolates and 14 non-blood isolates were found to be 52.63 and 57.96, respectively; these values did not differ significantly (P > 0.05). Nine non-blood strains (64.29%) of study group 2 and five blood strains (26.31%) of study group 1 were found to be positive for acid proteinase production; this difference was statistically significant (P < 0.05). Phospholipase production was found in five strains (26.31%) of the 19 blood isolates. None of the 14 non-blood strains exhibited phospholipase activity; this difference between the two groups was statistically significant (P < 0.05). In this study, correlations between adherence-phospholipase, and adherence-acid proteinase properties of strains were detected as well. In the present study, it has been observed that phospholipase production can be an important virulence factor in bloodstream infections caused by C. parapsilosis.
Keywords: Candida parapsilosis; enzymes; proteinase; phospholipase; adherence; CELL-SURFACE HYDROPHOBICITY; BUCCAL EPITHELIAL-CELLS; ALBICANS; PATHOGENICITY; EPIDEMIOLOGY; VIRULENCE; ADHESION